Implementasi Cyber Public Relations dalam Membangun Citra : Studi Deskriptif pada Instagram @lsf_ri Lembaga Sensor Film Republik Indonesia - Mutiah Apritawati; Nani Nurani Muksin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In the increasingly advanced digital era, Cyber Public Relations (Cyber PR) plays a crucial role in shaping an image without distance limitations. By leveraging Cyber PR, Public Relations practitioners can unlock significant potential. As the body responsible for film approvals in Indonesia, LSFRI must manage its image effectively to foster public trust. This study investigates how Cyber PR is implemented in shaping the image of LSFRI through the Instagram account @lsf_ri. The research adopts a qualitative, descriptive approach, guided by Bob Julius Onggo’s (2017) Cyber PR theory. Data collection methods include interviews as primary data and documentation as secondary data. The results of this study indicate that LSFRI maintains constant communication by posting content daily, and every post on the Instagram account @lsf_ri is always consistent with LSFRI's values related to the film industry; LSFRI does not respond quickly to all questions or comments on its Instagram; Instagram @lsf_ri does not target its Cyber Public Relations audience to the global market; The interactive communication conducted by the @lsf_ri Instagram account is considered effective; LSFRI's Cyber Public Relations activities on Instagram do not always facilitate two-way communication. Based on the results of this study, it is hoped that Cyber Public Relations on the @lsf_ri Instagram account will respond to every question or comment made by its followers and develop partnerships with other international institutions on Instagram specifically.